Antifungal of modified neolignans from Mitrephora wangii Hu - Sanyacharernkul S. (2017)
© 2016, The Korean Society for Applied Biological Chemistry. Chromatographic separation of leaves and twigs from M. wangii had led to the isolation of conocarpan (1) and 3′-methoxyconocarpan (2). These structures were assigned on the basis of spectroscopic methods. Compound 1 was modified by organic reactions and the modified compound 5 exhibited potent antifungal, Pyricularia oryzae. The method used poisoned food technique with mycelial growth inhibition for 14 days, 57 % (100 ppm). Compound 5 was stronger than mancozeb which the fungi toxicity drug used as a positive control.